Analisis Kritis Terhadap Fikih Perceraian Responsif Gender: Studi Penerapan Kaidah Maqasid al-Syari'ah - Holilur Rohman (AL-HUKAMA, 2020)
This study discusses the application of maqasid al-shar'ah principles in the gender-responsive marriage Jurisprudence. The focus of this research is: how the principles of maqasid al-shar'ah could be used as a foundation and approach of Ijtihad? How is the application of maqasid al-shar'ah principles in the issue of gender-responsive marriage Jurisprudence? This research is a qualitative research, which is in the form of descriptive-analytical library research. The approach used is the philosophical approach. In this study it was found that there are four rules of maqasid al-shar'ah which are used as the basis for jihad. These norms was then applied in a gender-responsive divorce Jurisprudence. This research concludes, that the holder of divorce rights is male, but the divorce can be pronounced based on the court's decision so that the results are more objective. In addition, divorce must be done for certain reasons, such as the cause of a constant dispute that cannot be resolved. Therefore, divorce without cause and without dialogue with his wife, is prohibited because it gives the effect of harm especially to his wife and children.